SOCIAL SUPPORT RECEIVED BY DIABETES MELLITUS TYPE II PATIENTS ATTENDING A COUNTY REFERRAL HOSPITAL IN KENYA. - Lugaya, Wilson; Mwenda, Mutunga; Syombua, Catherine; Washika, Esther (Journal of Health, Medicine and Nursing, 2022)
Purpose: Diabetes Mellitus Type II is a condition where the patients present with increased receptor resistance to adequately or normal amount of insulin production and reduced or inadequate amount of insulin produced. Worldwide the approximated burden of DM Type II is at 366 million people in 2011. The objective of the study is to determine the level of social support received by Diabetes Mellitus Type II patients attending a County Referral Hospital in Kenya. Methodology: This was a descriptive cross-sectional study conducted at a County Referral Hospital Outpatient Diabetic Clinic. Researcher administered questionnaires were used to collect data. Data analysis was manual for qualitative data and for quantitative data, descriptive statistics were used to analyze aided by the statistical package for social scientists (SPSS) version 22. Results: Majority 67.91% of the total participants reported not to be socially supported by their family and peers in specific aspects of their self-care management of Diabetes Mellitus Type II that contributed to the sub-optimal self-care practices attributed to the participants. Unique contribution to theory, practice and policy: Study found close relationship between adequate Diabetes Mellitus Type II self-care by DM Type II patients and social support. The researcher recommends in-cooperation of the patient's social circles in Diabetes Mellitus Type II self-care patients' education so as to promote understanding which will enhance social support hence optimal practice and adherence.